Alluvial terraces as a measure of vertical movements and neotectonics: evidences from Wadi Zazah, Al Jabal Al Akhdar, NE Libya - EL Oshebi , Farag M.; Badi, Adli M.; Shaltami, Osama R.; Fares , Fares F. (Libyan Journal of Science &Technology, 2022)
Wadi Zazah as part of the Al Jabal Al Akhdar Mountain has suffered numerous tectonic events throughout the geologic time. Wadi Zazah is one of the longest observable wadis that cut the lower escarpment and distributed fluvial terraces in different parts and locations. These terraces are shown with obvious variation in their elevations, some being higher, while others abruptly decreased in steps-like behaviour, where a series of steps and surfaces developed above and below the escarpment. Logically these terraces are explainable of odd and nonnatural occurring, hence the fluvial terraces in the wadi attributed and interpreted as terraces of a tectonic control, and ascribed to the effects of one of those tectonic episodes. Wadi Zazah due the fluvial terraces in this investigation can be considered as one of those morphotectonic valleys in Al Jabal Al Akhdar Mountain. The present work disagrees with the conclusion of previous work, which suggested that Wadi Zazah is a tectonically stable region.